2015
DOI: 10.1007/s40620-015-0217-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of miR-21, through targeting MKK3, may be involved in ischemia pretreatment protection from ischemia–reperfusion induced kidney injury

Abstract: miR-21 targets MKK3 in vivo and in vitro, inhibiting the downstream factors IL-6 and TNF-α. Therefore, miR-21 might be involved in protection of IPC against IR of the kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…In the other approach, several studies have suggested a reno-protective role for miR-21 and believe that upregulation of miR-21 plays a physiological role in protecting cells from acute injury by antiapoptotic effects and silencing metabolic functions. However, in chronic conditions, long-term elevation of miR-21 is detrimental and promotes cells toward infl ammation and fi brogenesis (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…In the other approach, several studies have suggested a reno-protective role for miR-21 and believe that upregulation of miR-21 plays a physiological role in protecting cells from acute injury by antiapoptotic effects and silencing metabolic functions. However, in chronic conditions, long-term elevation of miR-21 is detrimental and promotes cells toward infl ammation and fi brogenesis (39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Our data respectively showed the interactive network of lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA, which play a regulatory role as observed with mmu-miR-132-3p, mmu-miR-17-5p, mmu-miR-21a-5p, mmu-miR-21a-3p, mmu-miR-20a-5p, mmu-miR-93-5p, mmu-miR-185-5p and mmu-miR-874-3p. It is worth mentioning that miR-21, miR-223-5p, miR-125b and so on proved to be involved in IR-induced AKI, did not appear in our data [ 53 - 55 ]. The reason is that all ncRNA sequencing analysized were based on the lncRNA library, not built separate library of miRNA.…”
Section: Discussionmentioning
confidence: 74%
“…BUN and Scr in pediatric patients with AKI were decreased in parallel during hospitalization in all age groups [26]. BUN and SCr are both considered speci c markers to measure kidney function and pathological injuries after I/R [27]. SOD could limits oxidative stress and renal I/R injury and is considered as the most relevant molecule against I/R-induced changes [28].…”
Section: Discussionmentioning
confidence: 99%